Crafting Attributes of a Geological Now - Martin Bohle (Earth Science, Systems and Society)
Taking an Earth Science framework as its point of departure, this paper delves into the sociocultural ramifications of two distinct geological interpretations—epoch and event—of the contested but widely acknowledged term “Anthropocene.” While the term has gained considerable traction for encapsulating planetary-scale anthropogenic changes (PSAC), its meanings are varied, spanning scientific, philosophical, and cultural discourses. Earth scientists often examine PSAC through the lens of their discipline, yet the complex sociocultural implications attached to such geoscientific concepts call for an interdisciplinary perspective. Introduced by Crutzen and Stoermer in 2000, the term “Anthropocene” is designed to account for the transformative impact of modern societies on Earth System dynamics. Presently, two opposing viewpoints exist within geological discourse to describe PSAC: the “Anthropocene-as-an-event” concept, which underscores the accretion of human-induced changes, and the “Anthropocene-as-an-epoch” concept, focusing on a substantial alteration in Earth System dynamics. Utilising Renn’s theory of “The Evolution of Knowledge,” the paper posits these concepts as scientific borderline problems, catalysts for epistemic inquiries, linked to specific “economies of knowledge.” The ensuing analysis accentuates the multidimensionality of articulating PSAC from an Earth Science viewpoint, asserting that it not only mandates understanding the geological dimensions but also calls for integrating sociocultural and philosophical contexts. The paper concludes that geological terminology should consider associated cultural contexts of Earth Science to establish leadership for vital epistemic concepts.